2022
DOI: 10.1083/jcb.202109038
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic activators of apoptosis, necroptosis, and pyroptosis

Abstract: Targeted and specific induction of cell death in an individual or groups of cells hold the potential for new insights into the response of tissues or organisms to different forms of death. Here, we report the development of optogenetically controlled cell death effectors (optoCDEs), a novel class of optogenetic tools that enables light-mediated induction of three types of programmed cell death (PCD)—apoptosis, pyroptosis, and necroptosis—using Arabidopsis thaliana photosensitive protein Cryptochrome-2. OptoCDE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…We previously showed that periderm cells dying by opto-zfCaspase-8-induced apoptosis were also basally extruded from the periderm(Shkarina et al ., 2022). Thus, we analysed the behaviour of their actin cytoskeleton in larvae derived from a cross of Tg(Opto-caspase-8) with Tg(Krt4:Gal4_ UAS:mNG-UtrCH-UAS:Lyn-tagRFP) and found differences in the apical actin ridges behavior.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that periderm cells dying by opto-zfCaspase-8-induced apoptosis were also basally extruded from the periderm(Shkarina et al ., 2022). Thus, we analysed the behaviour of their actin cytoskeleton in larvae derived from a cross of Tg(Opto-caspase-8) with Tg(Krt4:Gal4_ UAS:mNG-UtrCH-UAS:Lyn-tagRFP) and found differences in the apical actin ridges behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptotic stimuli like geneticin have been shown to induce extrusion via sphingosine-1 phosphate (S1P) and its receptor, which is expressed in the surrounding cells. We have previously shown that S1P signaling does not seem to drive extrusion of pyroptotic cells in Caco-2 cell co-cultures (Shkarina et al, 2022), but so far it is unclear if S1P signaling or another mechanism activated downstream of the inflammasome is responsible for apical extrusion. Although the factors determining the direction of extrusion remain to be discovered, the different ratios of apical and basal extrusion of periderm cells in different zebrafish strains suggest a genetic component.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations